2018
DOI: 10.1002/pen.24966
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐Based Surfactant‐Aided Dispersion of Multi‐Walled Carbon Nanotubes in Epoxy‐Based Nanocomposites

Abstract: In this study, the dispersion of multi‐walled carbon nanotubes (MWCNTs) in epoxy was facilitated by an anionic surfactant, linear alkyl benzene sulfonic acid. Different types of composites were prepared using a fixed amount of MWCNTs (0.5 wt%), in absence of solvent/surfactant, in presence of solvent and solvent/surfactant. The composites were characterized using Fourier transform infrared spectrophotometer, thermogravimetric analyzer (TGA), differential scanning calorimeter (DSC), universal testing machine, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A significant change was absent in terms of shifting of the peak, but the intensity of the peak due to enzyme attack was found slightly diffused.4 Furthermore, for the epoxy, the presence of benzene and ester at the OH bond through a sharp broad peak was observed in the range of 3300–3500 cm −1 . [ 44 ] In case of EFS, the combination of both groups is relatively noticeable with the appearance of the same peak as found in both epoxy and RFS. The stretching vibration for PO 4 3− bond of hydroxyapatite in fish scale was observed at 1012 cm −1 .…”
Section: Resultsmentioning
confidence: 57%
“…A significant change was absent in terms of shifting of the peak, but the intensity of the peak due to enzyme attack was found slightly diffused.4 Furthermore, for the epoxy, the presence of benzene and ester at the OH bond through a sharp broad peak was observed in the range of 3300–3500 cm −1 . [ 44 ] In case of EFS, the combination of both groups is relatively noticeable with the appearance of the same peak as found in both epoxy and RFS. The stretching vibration for PO 4 3− bond of hydroxyapatite in fish scale was observed at 1012 cm −1 .…”
Section: Resultsmentioning
confidence: 57%
“…The degradation of the NE and epoxy‐based composites happens in the temperature between 350°C and 600°C. [ 30 ] The residual weight of the NE, E10PC, E20PC, E30PC, E40PC, and E30MPC composites was 3%, 11%, 10%, 27%, 30%, and 28%, respectively. From Table 2, it was found that the T onset temperature of the NE, E10PC, E20PC, E30PC, E40PC, and E30MPC composites was 345°C, 350°C, 350°C, 360°C, 350°C, and 361°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…At around 100 C, the composites go through weight loss due to the moisture and volatile elements absorbed by the composites during the preparation. Then, the dehydration of the composites occurs in between 100 C and 350 C. The degradation of the NE and epoxy-based composites happens in the temperature between 350 C and 600 C. [30] The residual weight of the NE, E10PC, E20PC, E30PC, E40PC, and E30MPC composites was 3%, 11%, 10%, 27%, 30%, and 28%, respectively. From Table 2, it was found that the T onset temperature of the NE, E10PC, E20PC, E30PC, E40PC, and E30MPC composites was 345 C, 350 C, 350 C, 360 C, 350 C, and 361 C, respectively.…”
Section: Ftirmentioning
confidence: 99%
“…As a result of this background study, we should return to redox-active organic materials for next-generation ESSs as electrode material, because they offer significant benefits over metal-based inorganic materials with respect of desired molecular structure, outstanding chemical and physical characteristics, and high electrochemical energy storage capabilities. [16,17] More specifically, redox-active conductive polymers (CPs) have been mostly used for ESSs instead of organic single molecules with the same redox moieties because of the benefits of polymeric materials, including superior stability, good processability, and ease of fabrication. [18,19] A conjugated bond structure along the polymer chain makes conducting polymers conductive.…”
Section: Introductionmentioning
confidence: 99%